Review of periurban agricultural concept and its place in solving food crisis of developing countries: a community development approach - Ibrahim, Muhammad Bello; Ahmad, Nobaya (Directory of Research Journals Indexing, 2014)
The place of agriculture in any economy is very vital, this paper attempts to review the concept of peri-urban agriculture (PUA) and its place as a contributor in solving urban food crisis in developing countries. Historical development and current happenings in peri-urban agriculture from different parts of the world were reviewed relating its role in solving ever increasing vegetable food demand in our urban centres. Agricultural communities participating in peri-urban agriculture are known the world over to have their relative multifunctional contributions to the effort of solving food crisis in our urban centres and contributing their quota to respective national economies. Different countries have their various approaches to PUA and it is the duty of the community to look at the function that will benefit their people the most. Lastly, the paper looked at how peri-urban agriculture through community and rural development can be used to boost urban food supply and one of the options for generating income to the farmers in developing countries.